2020
DOI: 10.1186/s43094-020-00076-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific variations in phytochemicals and antimicrobial potentiality of Dioscorea

Abstract: Background The monocotyledonous herbaceous crop Dioscorea is native to tropical and temperate regions of the world. Dioscorea tubers are dioecious in nature, have colossal therapeutic potentiality, and are frequently used in traditional medical practices throughout the world. Most of the research works are aimed to determine the medicinal property, nutritions, antinutrients, and biological activities of Dioscorea spp. without specifying the sexes of Dioscorea which promoted us to carry out this present researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The joint application of mycorrhizae with Azotobacter allows the fixed amounts of atmospheric nitrogen to be more remarkable because the fixing bacteria have a greater amount of available phosphorus (an essential element for the fixation of nitrogen), supplied by the activity of the solubilizing organisms was reported by Dixon and Kahn (2004) . The treatments in combination with chemical fertilizers proved to be better for total phenol (mg/100 g), one possible explanation of total phenol (mg/100 g) may be attributable to different factors such as genetic, climate, and environmental conditions ( Paul et al, 2020 ). The use of anthocyanin as a food colouring in ice cream, lemon juice, and hard candy in the food business highlights the significance of this antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…The joint application of mycorrhizae with Azotobacter allows the fixed amounts of atmospheric nitrogen to be more remarkable because the fixing bacteria have a greater amount of available phosphorus (an essential element for the fixation of nitrogen), supplied by the activity of the solubilizing organisms was reported by Dixon and Kahn (2004) . The treatments in combination with chemical fertilizers proved to be better for total phenol (mg/100 g), one possible explanation of total phenol (mg/100 g) may be attributable to different factors such as genetic, climate, and environmental conditions ( Paul et al, 2020 ). The use of anthocyanin as a food colouring in ice cream, lemon juice, and hard candy in the food business highlights the significance of this antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel extracted from a female plant ( Figure S2 ) and in reproductive phase ( Figure S3 ) shows more paclitaxel content. The study conducted by Paul et al 37 on Dioscorea tuber revealed the existence of sex-specific variations, with a greater accumulation of phytochemicals observed in the tubers of female plants as compared to male plants.…”
Section: Resultsmentioning
confidence: 97%
“…The study conducted by Paul et al 37 on Dioscorea tuber revealed the existence of sex-specific variations, with a greater accumulation of phytochemicals observed in the tubers of female plants as compared to male plants.…”
Section: Genotoxicity Testmentioning
confidence: 97%
“…However, most of the studies showed a low transformation and regeneration efficiency. This challenge is further compounded by the high genotype dependence of most tissue culture protocols and regeneration recalcitrance of some farmer preferred varieties (Paul et al, 2020). One possible way for mitigating this challenge in yam is to improve the transformation and regeneration efficiency using morphological regulator genes such as WUSCHEL2 ( Wus2 ), Baby boom (Bbm), and SHOOT MERISTEMLESS ( Stm ).…”
Section: Genetic Improvement Of Yammentioning
confidence: 99%